2020
DOI: 10.3991/ijet.v15i05.10967
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive e-Book for Physics to Improve Students' Conceptual Mastery

Abstract: Rotational dynamics is one of topic in physics for high school students that require visualization of its concepts. This research developed an interactive e-book for physics learning with its features consisting of multimedia content such as audio, video, animation, and simple problem-solving activities. This e-book has been validated and recommended by a team of experts. This trial aims to determine the effectiveness of e-book by students in mastering concepts, using a. quasi-experiment. The sample was chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…This study covered the development process of an interactive e-book based on the POE method by choosing "heat and temperature" from among physics topics. In the literature, a limited number of interactive e-books have been developed on physics, and they are related to energy sources (Hasan et al, 2018), static liquids (Adam & Suprapto, 2019), rotational dynamics (Adawiyah et al, 2019;Harjono et al, 2020), momentum (Septikasari et al, 2021), and earthquakes (Perwita & Fauzi, 2021). However, the literature review found no interactive e-books developed for the "heat and temperature" topic.…”
Section: The Processes Experienced During the Analysis Phasementioning
confidence: 99%
See 2 more Smart Citations
“…This study covered the development process of an interactive e-book based on the POE method by choosing "heat and temperature" from among physics topics. In the literature, a limited number of interactive e-books have been developed on physics, and they are related to energy sources (Hasan et al, 2018), static liquids (Adam & Suprapto, 2019), rotational dynamics (Adawiyah et al, 2019;Harjono et al, 2020), momentum (Septikasari et al, 2021), and earthquakes (Perwita & Fauzi, 2021). However, the literature review found no interactive e-books developed for the "heat and temperature" topic.…”
Section: The Processes Experienced During the Analysis Phasementioning
confidence: 99%
“…As research sample, previous studies in the interactive e-books field covered university students (Almekhlafi, 2021;Kao et al, 2019), preschool students (Li et al, 2020;Mouri et al, 2018;Sung & Wu, 2017), or primary school students (Huang & Liang, 2015;Hwang & Lai, 2017;Sung et al, 2019a, b;Umarji et al, 2020). There were a limited number of studies on physics subjects with high school students (Adam & Suprapto, 2019;Adawiyah et al, 2019;Harjono et al, 2020;Hasan et al, 2018;Perwita & Fauzi, 2021;Septikasari et al, 2021). In this sense, the interactive e-book developed in the study contributed to the literature on physics education at the high school level.…”
Section: The Processes Experienced During the Analysis Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Student learning outcomes in physics lessons on average are still unsatisfactory (Mbonyieyivuze et al, 2021). Motivation to learn physics must be increased through interactive learning (Harjono et al, 2020;Puspita et al, 2020). One of them is by utilizing modern technology such as mobile learning which can create a more pleasant learning atmosphere (Zakaria et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Buradan yola çıkarak etkileşimli e-kitap ve e-içerik gibi dijital eğitim teknolojilerinde kullanılmasının desteklenmesi önemlidir (Barate, Ludovico ve Mangione, 2014). Ancak ülkemizde teknoloji entegrasyonu için etkileşimli fen materyali (etkileşimli e- Alan yazına bakıldığında etkileşimli e-kitaplar alanında yapılan çalışmaların çoğunlukla etkileşimli e-kitabın öğrencilerin başarısına etkisine (Almekhlafi, 2021;Asrowi, Hadaya, ve Hanif, 2019;Hakkari ve diğ., 2017) ve öğrencilerin kavramsal öğrenmelerine etkisini (Harjono, Gunawan, Adawiyah ve Herayanti, 2020;O'Mahony, 2014)…”
unclassified